Ethical and Social Issues: A Literature Study on Management Problems in Information Technology - Rosidah (Jurnal Ilmu Komputer dan Sistem Informasi |JIKSI|, 2024)
The rapid advancement of information technology, particularly in the field of computer science, has significantly influenced ethical awareness in modern society. Ethical concerns in computer use are increasingly discussed due to growing public anxiety about privacy, data ownership, and access rights. While technological innovation provides substantial benefits, unethical practices such as software piracy, data manipulation, and privacy violations pose serious challenges. Computer ethics extends beyond technical issues it involves understanding how individuals and organizations apply moral principles when utilizing technology. This study investigates ethical and social problems in the management of information technology and examines the role of moral and social values in shaping ethical information system management. The findings emphasize the importance of ethical comprehension and awareness among technology users to promote responsible, transparent, and socially beneficial IT practices that align with both moral and legal standards.